2006
DOI: 10.1182/blood-2005-08-009357
|View full text |Cite
|
Sign up to set email alerts
|

Targeting self-antigens through allogeneic TCR gene transfer

Abstract: Adoptive transfer of T-cell receptor (TCR) genes has been proposed as an attractive approach for immunotherapy in cases where the endogenous T-cell repertoire is insufficient. While there are promising data demonstrating the capacity of TCRmodified T cells to react to foreign antigen encounter, the feasibility of targeting tumor-associated self-antigens has not been addressed. Here we demonstrate that T-cell receptor gene transfer allows the induction of defined self-antigenspecific T-cell responses, even when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 35 publications
1
68
2
Order By: Relevance
“…Previously, we have shown that gene transfer of MHC class I-restricted TCRs into CD8 ϩ T cells yields CTLs that strongly expand upon in vivo Ag encounter and that such cells can mediate tumor rejection in immunocompromised mice and break tolerance to defined self Ags (18,36). Collectively, the recent work by Morris et al (7) and our current experiments demonstrate that gene transfer of class I-restricted TCRs into postthymic CD4 ϩ T cells can be used to produce a pool of helper cells that can provide efficient help to CTLs in terms of expansion, tumor protection, and memory T cell formation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that gene transfer of MHC class I-restricted TCRs into CD8 ϩ T cells yields CTLs that strongly expand upon in vivo Ag encounter and that such cells can mediate tumor rejection in immunocompromised mice and break tolerance to defined self Ags (18,36). Collectively, the recent work by Morris et al (7) and our current experiments demonstrate that gene transfer of class I-restricted TCRs into postthymic CD4 ϩ T cells can be used to produce a pool of helper cells that can provide efficient help to CTLs in terms of expansion, tumor protection, and memory T cell formation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo function of TCR modified T cells has been studied extensively in mouse models. Data obtained in these studies indicate that both cytotoxic (6) and helper T cell compartments (7,8) with a defined Ag reactivity can be generated and these cells can expand to high numbers upon in vivo Ag encounter (6,9). Furthermore, infusion of TCR-modified T cells can be used to circumvent self-tolerance to defined self-Ags (9), including Ags expressed in spontaneous tumor models (M. de Witte, G. Bendle, M. van den Boom, M. Coccoris, T. Schell, S. Tevethia, E. Mesman, J.…”
Section: Long-term Functionality Of Tcr-transduced T Cells In Vivomentioning
confidence: 99%
“…The functionality of TCR-modified T cells during primary T cell responses in RIP-OVA high mice can be assessed by analyzing the development of type I diabetes as a consequence of destruction of pancreatic ␤ cells (9). Primary T cell responses in recipients of both TCR transgenic and TCR modified T cells resulted in destruction of insulin producing cells in 100% of the mice (data not shown).…”
Section: In Vivo Functionality Of Tcr-transduced T Cells During Seconmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward this goal, genetic modification of T cells with defined tumor-reactive TCR genes-an approach called TCR gene therapyhas been developed, first in mouse models (3,4) and more recently also in clinical trials (5)(6)(7). These clinical trials, primarily in patients with metastatic melanoma and synovial sarcoma, have demonstrated the feasibility of this approach, and in particular the targeting of the NY-ESO-1 Ag has shown encouraging clinical responses (7).…”
mentioning
confidence: 99%